Vaughan Williams and the soundscapes of Scott of the Antarctic - Carolyn Philpott; Elizabeth Leane; Douglas Quin (2020)
Vaughan Williams’s music for the 1948 Ealing Studios production Scott of the Antarctic has been recognized as one of the most outstanding film scores of its time. However, to date, it has received considerably less scholarly attention than the much more famous work it germinated, the Sinfonia Antartica (1949–52). While there have been some discussions of the film score within larger surveys of the composer’s oeuvre, these have not investigated the music to quite the same level of depth as that achieved in the separate studies of the Sinfonia Antartica undertaken by Michael Beckerman and Daniel Grimley. This lacuna is consistent, however, with the general treatment of Vaughan Williams’s film scores, which have tended to be overlooked or only addressed in passing in the scholarly literature.